Isolation and Characterization of Chalcone Synthase (CHS) Gene in Variegated-Flower of Dendrobium 'Enobi' and Phalaenopsis Hybrid Orchids - Linggabuwana, Aviesta; Putri, Saifa Usni; Kurniawan, Febri Yuda; Semiarti, Endang (HAYATI Journal of Biosciences, 2024)
Variegated flowers, characterized by the presence of different colors in flowers, have high economic and aesthetic values. The main pigment in the orchid's purple flowers is anthocyanin, while the chalcone synthase (CHS) gene is the key to anthocyanin biosynthesis. Analysis of the CHS gene can reveal some changes, including mutations, in the process of color patterning in flowers. This study aims to determine the structure of the CHS gene related to color patterning in Dendrobium 'Enobi' and Phalaenopsis hybrid with variegated flowers. The methods applied in this study are floral morphology observation, DNA isolation, CHS gene amplification, anthocyanin measurement, and bioinformatic analysis. Morphologically, the variegated pattern has appeared since the flowers were still in the bud on both orchids. Based on the anthocyanin content analysis, the difference in the genus is not directly related to the differences in the flower's anthocyanin content. In addition, the purple zone in the D. 'Enobi' and Phalaenopsis hybrid has a longer fragment of CHS than the white zone. Our analysis suggested several mutations in the white zone and differences in the type and location of several conserved domain proteins. Mutations at the CHS gene fragment might cause decreased anthocyanin pigment formation in the white region.